2012
DOI: 10.1177/1938640011434509
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening z-Osteotomy of the Fibula to Correct Persistent Talar Shift Following Open Reduction Internal Fixation of Ankle Fractures

Abstract: Therapeutic Level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…They reported that none of the patients who underwent this procedure presented progression towards arthropathy under x-ray after 34 months' monitoring. Thangarajah et al (2012), however, list the advantages of supra-syndesmotic Z-shaped osteotomy, performed in 4 patients with excellent results [15]. In 1998, Weber et al (1998) published a paper comparing the results obtained for a standard transverse osteotomy with a coronal plane Z-shaped osteotomy [6].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that none of the patients who underwent this procedure presented progression towards arthropathy under x-ray after 34 months' monitoring. Thangarajah et al (2012), however, list the advantages of supra-syndesmotic Z-shaped osteotomy, performed in 4 patients with excellent results [15]. In 1998, Weber et al (1998) published a paper comparing the results obtained for a standard transverse osteotomy with a coronal plane Z-shaped osteotomy [6].…”
Section: Discussionmentioning
confidence: 99%